Philosophy and ethics of aerospace engineering - Mendes, António Luis Martins (2017)
Engineering was a recognized human activity at a certain period of the history (17th / 18th centuries) when some militaries designed, constructed, operated, and maintained fortifications and engines of war, and then those activities were transferred into non-military applications. Engineering has continued to change geographically and socially and presently is extremely broad and its relevance it’s not solely technology based. However, its role in technology is decisive since is largely by technology that current society keeps its coherence. Philosophy of Technology has particularly attentive to the impact of technology on society and culture, rather than with technology itself. Actually, Philosophy has not paid adequate attention to engineering. On the contrary, at least since the 1960s, members of the philosophical community have been accusing engineers of polluting the natural world, transforming the climate, making useless consumer products, etc. Only in 1994 a new branch of Philosophy of Technology has emerged that is concerned with the technology itself, and may be called Engineering Philosophy of Technology or Philosophy and Ethics of Engineering. This is a new way of looking through engineering, that not only considers the ethical aspects but also many other modern issues that are being transformed by technical creations such as new existentialisms of risk projection, electronic networking, virtual reality, trans human and remote sensation and perception, graphic media presentations and probability analysis, interactive internet web sites, food, housing, transportation, communications, economics, etc. The present work starts with an expedition to the history of the Aeronautical Engineering in parallel with the Philosophy and Ethics in order to demonstrate the relationship between them. This thesis is intended to show the link between the aerospace/aeronautical engineering and world-wide economy growth (or lack of it!). This is done by analyzing some economic data in terms of world impact as well as the relevant social aspects such as the salaries of the airplane industry in the United States, France and Brazil, and their relation to the company income and country. These countries were selected due to their constant increase in state-of-the-art equipment proven in companies like Boeing, Airbus and Embraer.